2003
DOI: 10.1002/cm.10147
|View full text |Cite
|
Sign up to set email alerts
|

Vaults bind directly to microtubules via their caps and not their barrels

Abstract: Vaults are large (13 Mda) ribonucleoprotein particles that are especially abundant in multidrug resistant cancer cells and have been implicated in nucleocytoplasmic drug transport. To understand how these large barrel-shaped complexes are transported through the cytosol, we examined the association of vaults with microtubules both in vitro and in vivo. Within cells, a subpopulation of vaults clearly associates with microtubules, and these vaults remain associated with tubulin dimers/oligomers when microtubules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 44 publications
2
35
1
Order By: Relevance
“…As mentioned earlier, there are several observations that would argue that the vault complex is associated with the microtubular network, and perhaps vesicles along it, such as colocalization of MVP and secretory vesicles in neuron-like PC-12 cells (38) and the lysosomal marker CD63 (Lamp-3) in dendritic cells (40). An interesting finding by Eichenmuller et al (37) shows that vaults not only colocalize to microtubules but seem to directly interact with these structures via their structurally more complex cap regions. Two recent reports show the transport of MVP along microtubules (39,50).…”
Section: Discussionmentioning
confidence: 83%
“…As mentioned earlier, there are several observations that would argue that the vault complex is associated with the microtubular network, and perhaps vesicles along it, such as colocalization of MVP and secretory vesicles in neuron-like PC-12 cells (38) and the lysosomal marker CD63 (Lamp-3) in dendritic cells (40). An interesting finding by Eichenmuller et al (37) shows that vaults not only colocalize to microtubules but seem to directly interact with these structures via their structurally more complex cap regions. Two recent reports show the transport of MVP along microtubules (39,50).…”
Section: Discussionmentioning
confidence: 83%
“…Both cellular components co-purify from sea urchin cells [30], colocalise to the tips of PC12 neurits [113], and co-immunoprecipitate (with MVP) in non-small cell lung cancer cells [100]. A direct association of a subgroup of vaults with microtubules predominantly via the particle caps was demonstrated with 5 to 6 vaults binding each micron filament [116]. As in this study no vault-mediated crosslinking of microtubules was seen, the authors hypothesised that only one of the vault caps might be able to bind to the filament.…”
Section: Conformational States Intracellular Localisation and Movemementioning
confidence: 91%
“…However, this is to our knowledge the only hypothesis so far published that the two vault halves could be different. Mammalian vaults remained bound to tubulin di-and oligomers even after filament destruction by nocodazole [116], and tubulin was enhanced in the MVP immunoprecipitates after microtubule stabilisation with taxol [100]. However, the intracytoplasmic movement of vaults was only reduced but not completely blocked by nocodazole, suggesting that vault transport, though stimulated, is not entirely dependent on intact microtubules [100].…”
Section: Conformational States Intracellular Localisation and Movemementioning
confidence: 95%
“…Moreover, sea urchin vaults copurify with microtubules as described by Hamill and Suprenant (1997). In mammalian cells, vaults remain associated with tubulin oligomers even after nocodazol treatment (Eichenmüller et al 2003). Using an in vitro microtubule pull-down assay and negative staining, Eichenmüller et al (2003) have demonstrated that 5-6 vaults bind to 1-μm-long microtubules via their caps.…”
Section: Association Of Vaults With Microtubulesmentioning
confidence: 94%
“…Therefore, vault interactions with cytoskeletal elements and molecular motors may be necessary for vault transport over longer distances. An association of vaults with microtubules both in vivo and in vitro has been reported (Hamill and Suprenant 1997;Eichenmüller et al 2003). Furthermore, the colocalization of vaults and microtubules in PC12 and Chinese hamster ovary (CHO) cells has been described ).…”
Section: Introductionmentioning
confidence: 92%